Sonar findings of the uterus in patients on medroxyprogesterone acetate (Depo Provera) 150 mg injection - Louis A. de Wilde; Wilhelm J. Steinberg; Mariette Nel (South African Family Practice)
Background: Depo Provera (medroxyprogesterone acetate) 150 mg intramuscular injection every 12 weeks is one of the most common, effective, affordable and popular methods of contraception. Depo Provera shows excellent results in comparison to oral contraceptive agents as well as the contraceptive patch.